Water use by short rotation Eucalyptus woodlots in southern Rwanda - Mugunga, C.P.; Kool, D.; Wijk, Mark T. van; Mohren, G.M.J.; Giller, Kenneth E. (Springer, 2015)
Eucalyptus is abundant in Rwanda, mainly planted in short rotation woodlots, scattered in small clusters over the hilly landscape. A study was done in Butare and Busoro catchments, southern Rwanda from May to November 2007 to estimated water use of eucalypts in representative catchments in Rwanda, establishing a monthly water balance. We compared eucalypt water use to water use of other key crops in the study area and to that of eucalypts elsewhere. The woodlots had small coppice shoots ranging from 2 to 36 cm breast height diameter and potential tree transpiration recorded was 3 mm d−1. The annual potential tree transpiration was 10 % below annual precipitation. Dry month water deficit observed could be covered by reductions in leaf area, stomatal closure and changes in soil water storage. A sensitivity analysis showed that 50 % leaf area reduction corresponded to potential tree transpiration decline of 32.8 mm. The deficit may not impact tree growth negatively since dry seasons are usually not active for tree growth. The moderate eucalypt water use rate observed in this study may be a function of trees' small size and low tree stocking since such woodlots had less potential transpiration. The observed eucalypt water use rate is smaller than the range reported for eucalypts in Africa and was also smaller than that of key annual crops in the study area. Managing woodlots as short rotations and increasing initial tree spacing may contribute to resolving issues related to catchment hydrology associated with eucalypt plantations.